Analisis Program Corporate Social Responsibility dalam Menunjang Pencapaian SDGs (Studi Kasus CSR PT Solusi Bangun Indonesia Tbk Pabrik Cilacap) - Kusdiharta Kusdiharta (Pascasarjana Universitas Jenderal Soedirman, 2022)
This study shows that the Corporate Social Responsibility (CSR) Implementation Model of PT Solusi Bangun Indonesia (SBI) Tbk Cilacap Factory, which has the principle of the Triple Bottom Line (Planet, Profit, and people), uses a planning pattern that is synergistic with regional development planning patterns. There are program designs and objectives according to the theory presented by Cortez in the theory implementation program. The Government and Companies carry out Development Planning with a Top-Down model with the implementation using a Bottom-Up pattern with the participation of the community and academics. The Corporate Social Responsibility (CSR) program of PT Solusi Bangun Indonesia Tbk Cilacap Plant is by the objectives to be achieved by the local government through development and following the goals that the community needs to obtain as beneficiaries. The CSR program has an impact on the welfare of the community in a sustainable manner. PT Solusi Bangun Indonesia's CSR program is based on community empowerment which involves the community directly in the process. Several programs are implemented systematically, effectively, efficiently, and targeted manner. The CSR program of PT Solusi Bangun Indonesia Tbk Cilacap Plant results from collaboration and synergy between companies, local governments, and program recipients. Several programs impact the points of the Sustainable Development Goals in the Cilacap Regency. Based on this research, it can be said that PT Solusi Bangun Indonesia Tbk Cilacap Factory has implemented a CSR program that positively impacts regional development and the development of SDGs in the Cilacap Regency area. The CSR program has provided a sustainable improvement in community welfare per the regional development program in Cilacap Regency. The Pattern of Planning and Management of the CSR Program of PT Solusi Bangun Indonesia Tbk Cilacap Plant is expected to support the program to achieve national development goals broadly and become a universal reference for CSR implementation patterns in the private sector.